The role of parents on the prevention of dental disease in children: narrative review: Peran orang tua terhadap upaya pencegahan penyakit gigi pada anak: kajian pustaka - Sri Dwi Lestari; Melani Wulandhari; Indah Atika; Leny Sang Surya (Makassar Dental Journal PDGI Makassar, 2022)
Dental health in early childhood is one of the growth factors that need to be considered. The role of parents is very influential on the formation of children's behavior in maintaining dental and oral health because they interact most often with children, so it is hoped that their role is to educate children to behave properly in maintaining dental and oral health. This article is intended to analyze articles related to the role of parents in preventing dental disease in children, using a literature review design. Arti-cles were collected using Google Scholar, Pubmed and MEDLINE, with several keywords. The selected articles arepublished in 2012-2021, subject to children under 12 years old, available in full-text, and written in both Indonesian and English. It is con-cluded that parent are one of the most important elements in the development of health, especially children's dental and oral health in guiding, providing understanding andfacilities, and reminding to children in order to maintain dental and oral hygiene.